Impacts of traditional food consumption advisories: Compliance, changes in diet and loss of confidence in traditional foods - Knopper Loren D; McAuley Claire (BMC, 2011)
Abstract Background Food consumption advisories are often posted when industrial activities are expected to affect the quality and availability of traditional foods used by First Nations. We were recently involved in a project and asked to summarize details regarding the impacts of traditional food consumption advisories with respect to compliance, broader changes in diet and loss of confidence in traditional foods by people. Methods Our review was not conducted as a formal systematic comprehensive review; rather, we focused on primary and grey literature presenting academic, health practitioner and First Nations viewpoints on the topic available from literature databases (i.e., PubMed, Web of KnowledgeSM) as well as the internet search engine Google. Some information came from personal communications. Results Our overview suggests that when communicated effectively and clearly, and when community members are involved in the process, consumption advisories can result in a decrease in contaminant load in people. On the other hand, consumption advisories can lead to cultural loss and have been linked to a certain amount of social, psychological, nutritional, economic and lifestyle disruption. In some cases, communities have decided to ignore consumption advisories opting to continue with traditional lifestyles believing that the benefits of doing so outweigh the risk of following advisories. Conclusions We identified that there are both positive and negative aspects to the issuance of traditional food consumption advisories. A number of variables need to be recognized during the development and implementation of advisories in order to ensure a balance between human health, maintenance of cultures and industrial activity.